Faktor Minat Menjadi Technopreneurship di Kalangan Siswa Kejuruan: Analisis Bibliometrik - Fitri Ramadhani; Sumarno Sumarno; Gusnardi Gusnardi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Bibliometric analysis is a method for examining metadata derived from articles or journals, including information such as citations, authors, publication years, and countries (Andres, 2009). This analysis consists of three main stages: data collection, analysis, and communication. In the initial stage, data were collected using the Publish or Perish (PoP) application, drawing from the Scopus database with the keyword “technopreneurship” for the period 2014–2024. This study aims to explore the research landscape in the field of technopreneurship and technology-based entrepreneurship published in Scopus. For the query process, the search string TITLE-ABS-KEY (